(untitled) (مجلة الفاروق للعلوم, 2026)
This paper will cover the analysis of the possibility of transforming Martyrs’ Square in Tripoli into an ecological environmental square that puts into practice the principles of environmental sustainability. Squares are vital components within cities, contributing to enhancing urban competitiveness and forming an important part of the urban, social, historical and cultural fabric of the city. However, with the increasing environmental challenges and the absence of sustainability features in cities, urban planning needs to address this problem by focusing on developing such areas into sustainable ecological areas. Martyrs’ Square is one of the most important and largest squares in Tripoli, but it lacks environmental sustainability features. Through this paper, the theoretical concepts for transforming the urban environment in an integrated manner are reviewed, and the current situation of Martyrs’ Square is studied and analyzed. Then, it is proposed to integrate environmental sustainability practices to develop the square into an environmental square. Among these suggestions are the use of solar panels to provide a source of clean and renewable energy, and the use of natural materials and the place to reduce the environmental impact, in addition to relying on local plants to increase biodiversity and add water bodies to moderate the atmosphere and reduce temperatures. By integrating all these elements into the square, Martyrs’ Square can be developed into an environmental square that can enhance the principles of environmental and social sustainability. This article has reached the presentation of a model for developing Martyrs’ Square into an environmental square that can be implemented, and taken as a model to be followed and implemented in other locations to improve the urban environment by providing a healthy and sustainable environment for its citizens. The study recommends integrating eco-retrofitting strategies into urban planning policies, promoting renewable energy and green infrastructure in public squares, and strengthening community and governmental support to ensure long-term urban sustainability.